The Atomic, Molecular and Optical Science instrument at the Linac Coherent Light Source. (16th April 2015) - Ferguson, Ken R.; Bucher, Maximilian; Bozek, John D.; Carron, Sebastian; Castagna, Jean‐Charles; Coffee, Ryan; Curiel, G. Ivan; Holmes, Michael; Krzywinski, Jacek; Messerschmidt, Marc; Minitti, Michael; Mitra, Ankush; et al.
<x xml:space="preserve">Abstract</x> The Atomic, Molecular and Optical Science (AMO) instrument at the Linac Coherent Light Source (LCLS) provides a tight soft X‐ray focus into one of three experimental endstations. The flexible instrument design is optimized for studying a wide variety of phenomena requiring peak intensity. There is a suite of spectrometers and two photon area detectors available. An optional mirror‐based split‐and‐delay unit can be used for X‐ray pump–probe experiments. Recent scientific highlights illustrate the imaging, time‐resolved spectroscopy and high‐power density capabilities of the AMO instrument.